Food for teens: how social media is associated with adolescent eating outcomes. Issue 2 (30th July 2021) - Qutteina, Yara; Hallez, Lotte; Raedschelders, Maxime; De Backer, Charlotte; Smits, Tim
Abstract: Objective: To assess the relationship between exposure to social media food messages and self-reported adolescent eating outcomes (including food intake, perceived norms and food literacy). Design: A cross-sectional survey was used to assess reported exposure to core and non-core food messages (including marketing messages) on social media, as well as reported food intake, perceived norms, food literacy, attitudes, self-regulation, among others. Setting: 18 secondary schools across Flanders, Belgium. Participants: 1002 adolescents 11–19 years of age. Results: Self-reported exposure to food marketing and overall food messages on social media was positively associated with eating attitudes, behaviours, perceived norms and food literacy among adolescents. Interestingly, the relationship between food exposure and intake was shaped differently depending on food type; descriptive norms mediated the positive relationship between non-core food social media exposure and non-core food intake (e.g. indirect effect estimate on self-reported sweets consumption is 0·005, se 0·002, P < 0·01), while food literacy mediated the positive relationship between core food social media exposure and core food intake (e.g. indirect effect estimate on self-reported vegetable consumption is 0·01, se 0·003, P < 0·000). Conclusions: This study highlights the significance of social media in relation to adolescent eating. There is an opportunity for health professionals to use social media in the promotion of core food among adolescents. We call for relevant policy actions to regulate the marketing of non-core food to adolescents on social media.